Relocation of Westeuropean Enterprises in Bulgaria (Results of a Survey Among Foreign Investors) - Goev, Valentin (Research Papers, 2010)
In the study are presented results of questionnaire survey among the companies of foreign investors from Western Europe to Bulgaria. The aim of the study is to explore the opinions and judgments of foreign investors on the activities of their companies in Bulgaria. Important questions according to this aim are related with: motivation of foreign investors to locate their activities in Bulgaria, strategies for entering the Bulgarian market, identifying the types of foreign investors in Bulgaria, inter-firm relations with foreign investors and local enterprises-partners – their clients and suppliers.In the first part of the study are presented some basic formulations of the dominant theories of foreign investment, while the second part is entirely empirical and has sought answers to the above questions.